Réponses

2013-04-29T15:00:23+02:00

A=4x²-(x+3)(x-2)+2(x-2)

A=4x²-x²+2x-3x+6+2x-4

A=3x²+x+2

 

avec x=-5

A=3*(-5)²-5+2

A=75-5+2

A=72

 

avec x=1/2

A=3*(1/2)²+1/2 + 2

A=3/4+1/2+2

A=13/4

2013-04-29T15:03:10+02:00

a)  ( je remplace x par a )

A= 16a ² - a x a  + a x ( -2 ) + 3 x a + 3x --2 )  + 2a + 2 x ( -2)

    16a² - a²  -2a + 3a -6 + 2a - 4 

    = 15a² + a -6 + 2a -4

    15a² + 3a -10

 

b ) 

Pour x = -5

 A = ( 4 x -5 ) ² - ( (-5) +3 ) ( -5-2) + 2(-5-2)

     = -20² - (-5) x (-5 ) + (-5) x (-2)  +3 x -5 +3 x (-2 ) 

      = 400 - 25 + 10  -15 -6

        = 364